HUBUNGAN DUKUNGAN KELUARGA DAN KEPERCAYAAN DIRI TERHADAP KECEMASAN MENJELANG UJIAN AKHIR NASIONALPADA SISWA KELAS IX DI SMPN 1 JETIS MOJOKERTO - Akbar, Amar; F, Atmey (JURNAL KEPERAWATAN BINA SEHAT, 2015)
One of the causes less than optimal national final examination activities is a high level of anxiety in students that will carry out the national final examination. This research aims to know the relationship between family support and confidence with anxiety towards the national final examination. Facors affecting anxiety among other are lack of self-confidence or confedence and sosial support family. The research design used was Cross Sectional. The research sample was 9thgrade students in junior high school 1Jetis. The sample was selected using the proportionate stratified random sampling with the sample as much as 48 students. Research data obtained by using a measuring instrument in the form of the scale i.e. family support scale, confidence scale and scale of anxiety towards of national final examination which is a modification of the Zung Self-Rating Anxiety Scale (ZSAS). Result of calculation of regression with SPSS method produces the R value = 0,559, R square = 0,312 with ρ value (0,000) < 0,05 that shows there is a significant relationship between family support and confidence with anxiety towards of national final examination. Donations of family support and confidence against anxiety towards of national final examination is a 31,2% whereas the remaining 68,8% influenced by other factors. So it is advisable to institutions to establish a counseling facility for students in order for students grade 9thwho are experiencing anxiety not fall under the weight or panic so it doesn’t interfere with the activities of the national final examination.Key words: Family Support, Confidence, Anxiety towards The National Final Examination